Model Pengelolaan Wilayah Pesisir Dalam Rangka Pelestarian Hutan Mangrove - Arter Datunsolang (Universitas Negeri Jakarta, 2017)
This study aimed is to develop a model of coastal zone management that would be best to solve the problems. This study also to identify the bio-physical, social economic conditions of the coastal, and mangrove forests in the area. Using the dynamic system modeling version 2.5, the reseacher found several important conclusion. First, the potential of the coastal areas could be developed in a integrated system. It is based on the consideration that the results of the simulation model through dynamic systems showed changes in the condition of mangrove forests and socio-economic conditions of society. Second, institutional support and infrastructure are also needed for the management of mangrove forests. Local government needs to manage the coastal in a integration manner from all component and it has supported by regulation of local government itself.